Трехфононные взаимодействия и начальный этап эволюции фононного пучка в He II - Tucker, M. A. H.; Wyatt, A. F. G.; Zhukov, I. N. Adamenko,A. V.; Nemchenko, K. E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
Starting from the hydrodynamic Landau Hamiltonian we derived an expression for the characteristic rate of three-phonon processes in superfluid 4He, which is valid in the whole range of phonon energies where these processes are allowed. Possible limiting cases are analized and a comparison with the results of previous investigations is done. The three-phonon processes are turned out to govern completely the initial relaxation of a phonon pulse injected into He II by a heated solid. This results in an equilibrium phonon distribution in the anomalous region of phonon dispersion at times of the order 10-10s.